2016
DOI: 10.1155/2016/2641257
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nasopharyngeal Airway Device and Nasal Oxygen Tube in Obese Patients Undergoing Intravenous Anesthesia for Gastroscopy: A Prospective and Randomized Study

Abstract: Objective. This prospective and randomized study evaluated the efficacy and safety of the nasopharyngeal airway relative to the nasal oxygen tube in obese patients undergoing painless gastroscopy. Materials and Methods. Obese patients (BMI ≥ 28 kg/m2; n = 260) were randomly and equally apportioned to the nasopharyngeal airway (Group A) or nasal oxygen tube (Group B) group. Three patients were excluded due to failure of insertion of the nasopharyngeal airway. The duration of endoscopy, anesthetic dose, recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…Studies showed that using WNJ for oxygen supplement could decrease the use of jaw-lift maneuver significantly compared with nasal cannula oxygen,[2] and the SpO 2 reduction was significantly less in nasopharyngeal airway group than in nasal oxygen tube group. [5]…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that using WNJ for oxygen supplement could decrease the use of jaw-lift maneuver significantly compared with nasal cannula oxygen,[2] and the SpO 2 reduction was significantly less in nasopharyngeal airway group than in nasal oxygen tube group. [5]…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is the most common complication of gastroscopy with sedation 6 , and this event is caused by airway obstruction, decreased compliance of the chest wall, and respiratory depression. The incidence of hypoxia during gastroscopy with sedation has been reported to range from 1.8-69% [7][8][9] . In most cases, hypoxia is caused by airway obstruction, and lifting the jaw and increasing oxygen ow can improve hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the placement of a nasopharyngeal airway may be a good solution as it can be conveniently inserted and ensures an open airway [ 13 ]. A prospective randomized study by Xiao et al [ 14 ] evaluated the efficacy and safety of the nasopharyngeal airway relative to the nasal cannula in obese patients undergoing gastroscopy with intravenous anesthesia and showed that the amount of reduction in pulse oxygen saturation (SpO 2 ) from baseline during gastroscopy was significantly less in the nasopharyngeal airway group (6.03%) than in the nasal oxygen tube group (10.46%).…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been no study having determined the influences of supplement oxygen with the WNJT on respiration and ventilation during upper gastrointestinal endoscopy with propofol sedation or anesthesia in obese patients. In addition, placement of the WNJT is an invasive procedure and may result in a potential risk of nasal injury and bleeding [ 14 ]. Considering that there are limited data on the use of the WNJT during upper gastrointestinal endoscopy with intravenous sedation or anesthesia in obese patients and no study has assessed whether the WNJT performs better than the convenient nasal prongs for supplement oxygen in this condition, this RCT is designed to compare the efficacy and safety of the WNJT versus nasal prongs for supplementary oxygen during gastroscopy with intravenous propofol anesthesia in obese patients.…”
Section: Introductionmentioning
confidence: 99%